2018
DOI: 10.20546/ijcmas.2018.712.388
|View full text |Cite
|
Sign up to set email alerts
|

Carbon, Nitrogen Dynamics and Soil Organic Carbon Retention Potential after 18 Years by Different Land Uses and Nitrogen Management in RWCS under Typic Ustochrept Soil

Abstract: A long-term field experiment was conducted to design and implement alternative production systems with increased resource use efficiency, productivity and to determine the effect of tillage systems and mineral fertilizers on soil organic carbon patterns. This experiment intended to evaluate the effects of these management strategies on soil structural formation and structural stabilization of a sandy loam soil. The shift from puddled -transplanted rice on the flat land to raised bed systems affects the product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…While SOM's breakdown rate may be faster in the tropics, frequent inputs of organic modifications may promote SOM build-up [37]. Naresh et al [20] revealed that the highest SOC stock of 72.2Mg C ha -1 was found in F6 with T6 followed by that of 64Mg C ha -1 in F4 with T2 followed by that of F3 with T4 (57.9Mg C ha [38] reported that FYM applied 67.9 per cent of C stabilization in a rice-wheat system in the lower Indo-Gangetic plains.…”
Section: Distribution Of Organic Carbon Into the Soilmentioning
confidence: 99%
See 2 more Smart Citations
“…While SOM's breakdown rate may be faster in the tropics, frequent inputs of organic modifications may promote SOM build-up [37]. Naresh et al [20] revealed that the highest SOC stock of 72.2Mg C ha -1 was found in F6 with T6 followed by that of 64Mg C ha -1 in F4 with T2 followed by that of F3 with T4 (57.9Mg C ha [38] reported that FYM applied 67.9 per cent of C stabilization in a rice-wheat system in the lower Indo-Gangetic plains.…”
Section: Distribution Of Organic Carbon Into the Soilmentioning
confidence: 99%
“…Stable aggregates provide SOM with physical protection to minimize microbial attack [15]. Many agro-ecosystem studies have recorded the distribution of soil aggregates, soil aggregate stability, and aggregate-associated SOCs under various types of soil management, including no-tillage, fertilization, natural ecosystem conversion into agricultural land, and vice versa [18,19,20]. While the stability of soil aggregates and SOM sequestration are commonly related phenomena [21], their associations with land use transition, including agricultural abandonment, remain uncertain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A minimal input of 2.34 Mg C ha -1 yr -1 is needed to maintain SOC level. Naresh et al, (2018) reported that conservation tillage practices significantly influenced the total soil carbon (TC), Total inorganic carbon (TIC), total soil organic carbon (SOC) and oxidizable organic carbon (OC) content of the surface (0-15 cm) soil. Wide raised beds transplanted rice and zero till wheat with 100% (T 9 ) or with 50% residue management (T 8 ) showed significantly higher TC, SOC content of 11.93 and 10.73 g kg -1 ,respectively in T 9 and 10.98 and 9.38 g kg -1 , respectively in T 8 as compared to the other treatments.…”
Section: Soil Organic Carbon Soil Aggregation Vis-àvis Soil Organic Fractionsmentioning
confidence: 99%
“…The G+/Gratio was higher under NPSM treatment compared to other treatments, indicating that NPSM fertilization had changed soil microbial communities. Naresh et al, (2018) revealed that in the turning jointing stage, compared with CT, the ZT and FIRB treatments significantly increased nitrifying bacteria [Gn] by 77% and 229%, respectively. At the booting stage, the Gn rates in ZT and FIRB soils were 2.16 and 3.37 times greater than that in CT soil, respectively.…”
Section: Microbial Biomass Carbonmentioning
confidence: 99%